Measuring cultural diversity and its spatiotemporal evolution across Chinese provinces - Zhong, Mingxing (Frontiers in Human Dynamics, 2025)
The development of cultural pluralism represents a prevailing global trend, and investigating cultural diversity in China is pivotal for advancing the nation’s cultural prosperity strategy. This study measures aggregate, urban, and rural cultural diversity indices across China from 1990 to 2020, utilizing ethnic composition data from the Fourth to Seventh National Population Censuses of China and applying the Shannon-Wiener Diversity Index. Regional disparities and spatial correlations are further analyzed through the Dagum Gini coefficient, Moran’s I, and a gravity model. Key findings reveal: (1) China’s cultural diversity exhibits a continuous upward trend across all levels, with a consistent regional hierarchy of Western > Northeastern > Central > Eastern. (2) The national Gini coefficient demonstrates a persistent decline at all levels. Subregional variations include: the Eastern region showing the steepest decline; the Northeastern region displaying an increasing trend; the Western region experiencing slight growth in urban areas but minor declines in aggregate and rural measures; and the Central region recording a marginal aggregate decrease alongside continuous rises in urban/rural disparities. These results underscore pronounced interprovincial heterogeneity in cultural diversity distribution. (3) Spatial autocorrelation analysis identifies intensifying clustering patterns, with the Western region forming “high-high” clusters and the Eastern region exhibiting “low-low” agglomerations. (4) Interregional connectivity, as quantified by the gravity model, grows increasingly complex and dense, ultimately evolving into a C-shaped strong linkage network spanning northern-western-southern China. This study provides empirical insights for fostering ethnic cultural integration and supporting China’s cultural power strategy.